On Linial’s Conjecture for Split Digraphs - Sambinelli, Maycon; da Silva, Cândida Nunes; Lee, Orlando (Anais do Encontro de Teoria da Computação (ETC); 2016: Anais do I Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2016.9748, 2016)
In this paper we show that Linial’s Conjecture holds for two classes of split digraphs, namely the spider digraphs and the k-loose digraphs.